Freedom of speech in media communication. The censorship and politicisation of media institutions - Mariana TOCIA (Diversitate si Identitate Culturala in Europa)
Starting from the classic ethical problems and reviewing the modern regulated ethical norms regarding freedom of speech and its limitations in media communication, the current paper aims to verify the following hypotheses in media communication: (1) Alerting European Court of Human Rights (ECHR) of the infringement on freedom of speech entails a positive response for journalists who fight for this right, (2) Press censorship is the result of editorial policy and the political orientation of the press, which can generate mass resignations of journalists, (3) The more politicised the media institutions, the more limited the right to freedom of speech is for journalists.